2005
DOI: 10.1149/1.1839531
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Properties of P(VdF-HFP)-Based Fibrous Polymer Electrolyte Membrane Prepared by Electrospinning

Abstract: Microporous fibrous membranes were prepared from poly(vinylidenefluoride-co-hexafluoropropylene) P(VdF-HFP) solutions in an acetone/N,N-dimethylacetamide mixture using the electrospinning method. Varying the P(VdF-HFP) polymer concentration in electrospinning can easily control the pore size and the porosity of the electrospun fibrous membranes (ES-FMs). The usefulness of the ES-FMs as a matrix of polymer electrolyte for a lithium-ion polymer battery with high performance was evaluated. Electrospun fibrous pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(53 citation statements)
references
References 19 publications
3
47
3
Order By: Relevance
“…It was also found that the formation of interconnected web structure via heat treatment improved both the mechanical properties and dimensional stability of nanofiber membranes [259,260] . Similar results were also obtained using poly(vinylidene fluoride-co-hexafluoropropylene) P(VdF-co-HFP) nanofiber membrane as separator [261][262][263] .…”
Section: Batteriessupporting
confidence: 78%
“…It was also found that the formation of interconnected web structure via heat treatment improved both the mechanical properties and dimensional stability of nanofiber membranes [259,260] . Similar results were also obtained using poly(vinylidene fluoride-co-hexafluoropropylene) P(VdF-co-HFP) nanofiber membrane as separator [261][262][263] .…”
Section: Batteriessupporting
confidence: 78%
“…The narrow range of porosity of these membranes is the result of the electrospinning parameters that lead to close similarities in the membrane morphologies and interlaying of the fibers. The values of porosities are higher than those reported in some earlier works [25,30]. Fig.…”
Section: Porosity Electrolyte Uptake and Electrolyte Retentioncontrasting
confidence: 58%
“…where M m is the mass of the dry membrane, M BuOH is the mass of n-butanol absorbed, BuOH and P are the densities of n-butanol and polymer, respectively [25].…”
Section: Characterization Of Electrospun P(vdf-hfp) Nanocomposite Memmentioning
confidence: 99%
“…The porosity (P) is an important parameter for separators as it influences the electrolyte uptake and ionic conductivity [21,22]. The quantitative analysis is conducted here by using the n-butanol uptake method and calculated as [23]:…”
Section: Morphology Porosity Electrolyte Uptake Swelling and Ionicmentioning
confidence: 99%